Effect of four fluoroquinolones on the viability of bladder cancer cells in 2D and 3D cultures - Kloskowski, Tomasz; Fekner, Zuzanna; Szeliski, Kamil; Paradowska, Michelle; Balcerczyk, Daria; Rasmus, Marta; Dąbrowski, Paweł; Kaźmierski, Łukasz; Drewa, Tomasz; Pokrywczyńska, Marta (Frontiers in Oncology, 2023)
The anticancer properties of fluoroquinolones and the high concentrations they achieve in urine may help in bladder cancer therapy. This study aimed to analyze the properties of 4 fluoroquinolones as potential candidates for supportive treatment of bladder cancer. Comparative analyses were performed on the cytotoxic effects of norfloxacin, enrofloxacin, moxifloxacin, and ofloxacin on normal and cancer urothelial cell lines. In 2D culture, the cytotoxic properties of fluoroquinolones were evaluated using MTT assays, real-time cell growth analysis, fluorescence and light microscopy, flow cytometry, and molecular analysis. In 3D culture, the properties of fluoroquinolones were tested using luminescence assays and confocal microscopy. All tested fluoroquinolones in 2D culture decreased the viability of both tested cell lines in a dose- and time-dependent manner. Lower concentrations did not influence cell morphology and cytoskeletal organization. In higher concentrations, destruction of the actin cytoskeleton and shrinkage of the nucleus was visible. Flow cytometry analysis showed cell cycle inhibition of bladder cancer cell lines in the G2/M phase. This influence was minimal in the case of normal urothelium cells. In both tested cell lines, increases in the number of late apoptotic cells were observed. Molecular analysis showed variable expression of studied genes depending on the drug and concentration. In 3D culture, tested drugs were effective only when the highest tested concentrations were accompanied by caspase 3/7 activation and cytoskeleton degradation. This effect was hardly visible in non-cancer cell lines. According to the data, norfloxacin and enrofloxacin had the most promising properties. These two fluoroquinolones exhibited the highest cytotoxic properties against both tested cell lines. In the case of norfloxacin, almost all calculated LC values for bladder cancer cell lines were achievable in the urine. Enrofloxacin and norfloxacin can be used to support chemotherapy in bladder cancer patients.